Association between hematological profile and serum 25-hydroxyvitamin D levels and FokI polymorphism in individuals with cystic fibrosis - Coelho de ASSIS, Milena Luana; Braga CARTAXO, Constantino Giovanni; de Carvalho COSTA, Maria José; Marques QUEIROZ, Dayanna Joyce; Carmati PERSUHN, Darlene; Rodrigues GONÇALVES, Maria da Conceição (Revista de Nutrição, 2023)
Objective The present study aimed at investigating the association between hematological profile and serum 25-hydroxyvitamin D (25[OH]D) levels and Fokl polymorphism of the vitamin D receptor gene in individuals with Cystic Fibrosis. Methods A cross-sectional study that involved 18 men and women aged 0-25 years with Cystic Fibrosis. Socio-demographic information and the factors associated with sun exposure were obtained. Weight, height, and arm circumference were also measured. Blood sample was collected for the analysis of biochemical parameters (25[OH]D, parathyroid hormone, and calcium levels and blood count) and for the validation of the presence of FokI polymorphism in the vitamin D receptor gene. Results Among the participants, 33.33% (n=6) had vitamin D deficiency (19.60±6.180 ng/mL), and 27.8% (n=5) presented with anemia and low weight for age. In terms of genotype, 5.6% (n=1) presented with the FF genotype, 72.3% (n=13) had the Ff genotype, and 22.2% (n=4) had the ff genotype. Serum 25(OH)D levels were associated with hemoglobin (p=0.008) and hematocrit (p=0.019) levels and leukocyte count (p=0.0114). No association was observed between 25(OH)D levels and the genotypes (FF, Ff, and ff) (p=0.2451). In addition, an association was observed between FokI polymorphism and the total leukocyte count (p=0.01). Conclusion An association was observed between serum 25(OH)D levels and hemoglobin and hematocrit levels and leukocyte count in individuals with Cystic Fibrosis. Moreover, FokI polymorphism was associated with total leukocyte count.